Synthesis and Spectrophotometric Study of Some New Azodyes Derived From 4,5-diphenylimidazole - Ali, Asaad A (University of Thi-Qar Journal of Science, 2019)
This study involves the preparation of three azodyes 2-( sulfapyridineazo)- 4,5-diphenyl imidazole (M1) , 2-( 2-arsonophenylazo)-4,5-diphenyl imidazole (M2) and 2-( sulfapyridineazo)- imidazole (M3) , they have been described by C.H.N. , I.R. and Visible spectroscopic techniques. The acid-base properties were studied at different pH values (0.65-12) , then the ionization and protonation constants were determined. The solvents effect were studied at different solvents polarities